Eksistensi Konselor: Manifestasi Pendidikan Era Millenial - Yaumil Afiat (Program Studi Bimbingan dan Konseling FKIP UMSU, 2020)
Guidance and counseling is an integral part of education. Through education, it is expected that students as a generation of millennial will be able to become creative and innovative people. In order to realize the goals of education, counselors in the delivery of services in schools contribute and contribute in efforts to help students carry out their developmental tasks. The ability of students in the millennial is accompanied by the competence of counselors in performance in the field as a manifestation of education in schools. This paper give an idea of how the existence of counselors in the millennial to realize the goals of education